Efficient blue organic electrochemiluminescence luminophore based on a pyrenyl–phenanthroimidazole conjugate. Issue 54 (15th June 2022) - Kim, Kwang-Myeong; Kim, Jiwoo; Kim, Joohoon; Hong, Jong-In
Abstract : A pyrenyl–phenanthroimidazole conjugate exhibited strong blue electrochemiluminescence via the reductive–oxidation co-reactant pathway. Abstract : A pyrenyl–phenanthroimidazole (Py–PI) conjugate emitted strong blue electrochemiluminescence (ECL) emission via the reductive-oxidation co-reactant pathway, with an ECL efficiency 3.3 times higher than that of the 9, 10-diphenylanthracene (DPA) reference compound.